2011
DOI: 10.1063/1.3646743
|View full text |Cite
|
Sign up to set email alerts
|

Analytic criteria for shock ignition of fusion reactions in a central hot spot

Abstract: Shock ignition is an inertial confinement fusion scheme where the ignition conditions are achieved in two steps. First, the DT shell is compressed at a low implosion velocity creating a central core at a low temperature and a high density. Then, a strong spherical converging shock is launched before the fuel stagnation time. It increases the central pressure and ignites the core. It is shown in this paper that this latter phase can be described analytically by using a self-similar solution to the equations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…We first make use of a result by Ribeyre et al [9] who give an approximation to the velocity of a Lagrangian fluid element following the passage of the spherical shock wave. This is used as a boundary condition in a 1D spherical fluid model [10], set to model an ideal fluid with no dissipation apart from the shock itself.…”
mentioning
confidence: 99%
“…We first make use of a result by Ribeyre et al [9] who give an approximation to the velocity of a Lagrangian fluid element following the passage of the spherical shock wave. This is used as a boundary condition in a 1D spherical fluid model [10], set to model an ideal fluid with no dissipation apart from the shock itself.…”
mentioning
confidence: 99%
“…In these designs, shock pressures at shock launch time vary from $300 Mbar to $700 Mbar. The shocks are strongly amplified by spherical convergence by amounts that depend on the details of the implosion 813,816 and may reach pressures of the order of 1-3 Gbar at shock collision time. 809,816 The shock is further amplified by the shock collision.…”
Section: A One-dimensional Analysis and Simulationsmentioning
confidence: 99%
“…Betti et al indicated that a hot-spot pressure enhancement of 70% compared with that expected in typical hot-spot implosions can lead to a fourfold reduction in the energy required for ignition. Ribeyre et al 813 derived a criterion for ignition based on the strong-shock velocity and pre-spike fuel-assembly density and radius. One-dimensional theoretical models of shock propagation and shock collision in planar 814 and spherical 813,[815][816][817] geometries have characterized parameters for achieving maximum amplification of the hot-spot pressure.…”
Section: A One-dimensional Analysis and Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We provide an outline here of the construction of the symmetric piston, a more complete explanation can be found in Davie and Evans. 4 We first make use of a result by Ribeyre et al 13 who give an approximation to the velocity of a Lagrangian fluid element following the passage of a strong, spherically converging shock wave. This is used as a boundary condition in a 1D spherical fluid model, 14 set to follow an ideal fluid with no dissipation apart from the shock itself.…”
Section: Code Initialisation For Spherically Converging Shocksmentioning
confidence: 99%